Analisis Unsur Riba Dalam Sistem Pembayaran Paylater Berdasarkan Perspektif Hukum Ekonomi Syariah - Fitriani, Sheila Aida; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the existence of usury elements in the PayLater payment system from the perspective of Islamic economic law. PayLater services are increasingly in demand in various marketplaces because they provide convenience in transactions with an installment system without the need for a credit card. This payment method allows users to buy goods or services in advance and pay for them later with an installment scheme. However, in Islamic teachings, this system needs to be further analyzed because it has the potential to contain usury, which is prohibited in Islamic law. This study aims to evaluate whether PayLater contains usury elements and assess its compliance with the principles of the qardh contract in Islam. Using normative legal methods and a qualitative approach based on literature studies, this study examines related literature, fatwas, and regulations. The results of the study show that in practice, PayLater charges interest, late fees, and additional fees, which are categorized as jahiliyah usury. This is contrary to the principles of the qardh contract, which requires loans to be returned according to the principal amount without additional payments. Therefore, the PayLater system needs to be evaluated and adjusted so that it continues to provide convenience without violating the principles of Islamic economic law.